(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
Heteropneustesfossilis, Clariasbatrachus and C. gariepinus are three major catfishes ofecological and economic importance. Identification of these fish species becomes aproblem when the usual external morphological features of the fish are lost or removed,such as in canned fish. Also, newly hatched fish larva is often difficult to identify. PCRsequencingprovides accurate alternative means of identification of individuals at specieslevel. So, 16S rRNA genes of three locally collected catfishes were sequenced after PCRamplification and compared with the same gene sequences available from othergeographical regions. Multiple sequence alignment of the 16S rRNA gene fragments ofthe catfish species has revealed polymorphic sites which can be used to differentiate thesethree species from one another and will provide valuable insight in choosing appropriaterestriction enzymes for PCR-RFLP based identification in future. Asiat. Soc. Bangladesh, Sci. 41(1): 51-58, June 2015